Implications of Learning Models Cooperative Numbered Heads Together (NHT) Assisted by Power Point Media on Learning Outcomes Students - Rosmawati, Rosmawati; Nuraedah, Nuraedah; Idrus, Idrus (Journal of Education Method and Learning Strategy, 2024)
Education also plays a role role important for nation because education seen as effort enlighten man with prepare generation successor nation that has qualifications and skills. Formulation problem is Learning Model implications The Numbered Heads Together (NHT) Cooperative Assisted by Power Point Media is influential Regarding Learning Outcomes Students in Class IV Social Sciences Subjects at Lereea State Elementary School Subdistrict Bahodopi Regency Morowali. Research purposes know Learning Model implications The Numbered Heads Together (NHT) Cooperative Assisted by Power Point Media is influential Regarding Learning Outcomes Students in Class IV Social Sciences Subjects at Lereea State Elementary School Subdistrict Bahodopi Regency Morowali. Research methods experiment is method research conducted​with experiment, which is used for know influence variable independent (treatment) towards variable dependent (result) in controlled conditions.​ Results of data analysis in research this made based on the data obtained from activity study. Study this held 5 meetings.​ At the meeting First, students given a pretest in class experiment.